Reproductive Conditioning of the Peruvian Scallop Argopecten purpuratus in Different Environments - Rafael Octavio Crisóstomo; Renzo Pepe-Victoriano; Sheda Méndez-Ancca; Abel Walter Zambrano-Cabanillas; Olegario Marín-Machuca; Hernan Mauricio Perez; Víctor Yana-Mamani; Mario Ruiz-Choque (Fishes, 2023)
Obtaining viable Argopecten purpuratus seeds faces challenges, especiallyci the unpredictability of the marine environment and high production costs in hatcheries. However, improving the method of "Broodstock Conditioning In Hatcheries" is key to ensure permanent seed supplies by minimizing the dependence on marine conditions and by maximizing economic viability in hatcheries. In an effort to overcome these barriers, broodstock were conditioned into two different environments: (a) Natural Environment: Natural marine conditions located in Bahía Inglesa, Atacama Region, Chile. (b) Hatchery: Laboratory conditions to achieve gonadal maturation, spawning induction, fertilization and larval development. The purpose of this research was to evaluate how the type of reproductive conditioning affects the reproductive potential and nutritional quality of the progeny. Both methods were successful at inducing the necessary maturity for reproduction, obtaining viable gametes and larvae. On the other hand, it was observed that in the natural environment, the oocytes and D larvae reached a greater size and nutritional value, being the most significant differences with (p < 0.05): the size of the D larvae reached figures of 95.8 ± 3.1 <semantics>μm</semantics> and 91.2 ± 2.7 <semantics>μm</semantics> in the environment and hatchery, respectively; the lipid content in dry mass was 25.2 ± 3.1 mg g<semantics>−1</semantics> and 13.5 ± 1.9 mg g<semantics>−1</semantics> for the natural environment and hatchery, respectively. Although quality indicators in hatcheries were slightly lower compared to the natural environment, the possibility of conditioning A. purpuratus broodstock independently of environmental variability highlights the importance of further optimizing broodstock conditioning aspects in hatcheries that would allow more predictable and sustainable production.